Childhood morbidity and adulthood ill health. Issue 1 (March 1990) - Power, C; Peckham, C
Abstract : STUDY OBJECTIVE–The aim of the study was to investigate the relationship between the state of health in childhood and ill health in early adult life. DESIGN–The study used data collected as part of the National Child Development Study and related health at 7 years of age to that at 23. A wide range of information on child health in the cohort was available, which was used to construct a broader measure of health status than selected diagnostic categories. SETTING–The survey population was nationwide. PARTICIPANTS–The study population included all children born in the week 3-9 March 1958. They were followed up at 7, 11, 16, and 23 years. Of the target population of 17, 733 births, 12, 537 (76%) were retraced and interviewed at 23. MEASUREMENTS AND MAIN RESULTS–Children at age 7 were allocated to 13 morbidity groups; 20% of children had reported no ill-health apart from the common infectious diseases, but 10% were included in four or more of the morbidity groups. Children with no reported morbidity retained their health advantage into early adulthood: ratios of observed to expected ill health for four of the five indices examined at age 23 were all significantly below one (self rated health 0.81, asthma and/or wheezy bronchitis 0.63, allergies 0.79, emotional health 0.75). Children with more morbidity at age 7 had higher ratios of ill health in adulthood. A chronic condition in childhood was associated not only with excess morbidity in the short term but also with a poor health rating in early adult life (ratio = 1.38). Morbidity was significantly increased for most of the adulthood indices among children with asthma and/or wheezy bronchitis. However most ill health in young adulthood occurred in study members with a relatively healthy childhood. CONCLUSIONS–Although the state of health in childhood has long term implications, it does not form a substantial contribution to ill health in early adult life.